Legal regulation of martial law in the Republic of Belarus and the Russian Federation: comparative analysis - Utjashov, Eduard K. (Journal of the Belarusian State University. Law, 2019)
The subject of the conducted research is a comparative analysis of the two allied countries legislations on legal regulation of the martial law regime. The purpose of the article is to find out the common and special rules of law in the content of these legislations and to identify the common basis, principles, rules, methods of its regulation. Such an analysis allows the Republic of Belarus and the Russian Federation to conduct the coordinated legal, political, military actions and to make the necessary arrangements in order to carry out the the martial law regime. The article also determines the comparative uncertainty of some foundations of introducing the martial law regime, the existence of the evaluated and abstract rules, which determine the margin of appreciation of public authorities while interpreting the rules of law. Margin of appreciation may cause the mismatch of the government departments’ actions of the two countries while conducting the martial law regime. It is analyzed the causes of the inevitable appearance of the legal vacuum in the legislations of the two countries concerning the martial law regime; thus it’s formulated a scientific problem – to formulate and to justify the fundamental principles of the law which can be applied in a state of martial law. There are showed all the possible conflicts of law and proposals to overcome them. First of all it’s about the contradictions between the constitutional rules of law, which prohibit the censorship authorities, and the rules of martial law regime, which may contain the permission of its establishment. The author proposes to determine the balance of rights limitation in the private sector at the legislative level in comparison with the revealing of the level of forces and means needed for the state to reflect the aggression or attack, taking into account the level and scale of military conflict.